1998
DOI: 10.1002/(sici)1096-8628(19981102)80:1<42::aid-ajmg7>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Atypical manifestations of two cases of trisomy 9 syndrome: Rethinking development delay

Abstract: Trisomy 9 syndrome is characterized by "bulbous" nose, microphthalmia, dislocated limbs, and other anomalies of skeletal, cardiac, genitourinary, and central nervous systems. With the exception of one reported case study, all surviving infants have had severe mental impairment. The prospect of severe mental retardation often overwhelms parents who are faced with prenatal diagnosis of trisomy 9. We report on two new cases of mosaic trisomy 9, both of whom are only mildly developmentally delayed. One patient pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…This type of observation is not uncommon, especially for mosaic syndromes. Saneto et al [1998] reported two atypical cases of mosaic +9. These two were mildly retarded, and one patient had strikingly normal facial features with 82% mosaicism of +9, although severe mental retardation is common in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…This type of observation is not uncommon, especially for mosaic syndromes. Saneto et al [1998] reported two atypical cases of mosaic +9. These two were mildly retarded, and one patient had strikingly normal facial features with 82% mosaicism of +9, although severe mental retardation is common in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, Shokeir published two reports documenting probable autosomal recessive inheritance in specific ethnic groups. 10,11 Others have noted the high incidence of cardiac defects in first-degree relatives, 12 as well as the frequent co-occurrence in up to three-tenths of cases with well defined genetic and chromosomal anomalies, 13 including Turner's syndrome, 14 mosaic deletions of chromosome 22, 15 trisomy 9, 16 and terminal deletions of chromosome 11. 17 Biochemically, decreased levels of platelet-derived growth factor have been reported in surgical samples from hypoplastic hearts.…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…A second case with full trisomy 9 had a hypoplastic anus and genital anomalies [Cantu et al, 1996]. The third case had a mosaic trisomy and a stenotic anus [Saneto et al, 1998]. Two additional cases have abnormal placement of the anus [Anneren and Sedin, 1981; Diaz‐Mares et al, 1990].…”
Section: Introductionmentioning
confidence: 99%